Educational strategies for preventing foot ulcers in people with diabetes mellitus: an integrative review - Oliveira, Dara Cesario (2020)
Objective: to identify educational strategies to prevent foot ulcers in people with diabetes mellitus. Method: this is an integrative review conducted between December 2019 and January 2020 using PUBMED, LILACS, COCHRANE and SCOPUS databases and the descriptors Health Education, Foot Ulcer, Diabetes and Nursing. 19 primary articles were included. Results: there were 12 educational strategies that were implemented to prevent foot ulcers in people with diabetes: health education, educational programs with pamphlets, follow-ups and PowerPoint for presentation of seminars, information brochures, diabetic foot exam with guidelines. self-care, motivational interviews, motivational videos, educational interventions, educational workshops / workshops, small message services, educational groups, individualized education and educational brochure. Conclusion: Health professionals can use different educational strategies, in different health settings to prevent foot ulcers in people with diabetes, in a simple, effective and accessible way.